PENYULUHAN KESEHATAN TENTANG PEMERIKSAAN SADARI (Pemeriksaan Payudara Sendiri) PADA POSBINDU ANGGREK BULAN DAN POSBINDU DELIMA SENJA SEBAGAI UPAYA PENINGKATAN PENGETAHUAN DAN KETRAMPILAN DETEKSI DINI KANKER PAYUDARA - Retno Yulianti; Tiwuk Susantiningsih; Andri Pramesyanti Pramono; Nunuk Nugrohowati (LPPM UPN Veteran Jakarta, 2018)
Breast cancer is one type of cancer that ranks first in Asia and in Indonesia with a relative frequency of18.6%. Breast cancer also occupies the top 5 positions for causes of cancer deaths. Many breast cancer sufferersare found clinically with advanced stage symptoms, so they need special attention. In fact, breast cancer can beovercome if the patient begins to detect and treat it early. Early efforts to carry out breast cancer screening arewith the BSE program or self breast examination. Counseling was carried out at Posbindu Anggrek Bulan andPosbindu Delima Senja. The implementation of this service activity uses a method of counseling, video playbackand simulation that is very good for providing knowledge and skills related to health education to the community.There is an increase in knowledge of the material given through the pretest and posttest. Self-awareness skills asbreast cancer prevention efforts were carried out well by participants. The results of community service activitiesare expected to get a lot of information about breast cancer as well as overall female reproductive healthinformation.